2007
DOI: 10.1016/j.jhazmat.2006.06.115
|View full text |Cite
|
Sign up to set email alerts
|

Effects of exposure time and co-existing organic compounds on uptake of atrazine from nutrient solution by rice seedlings (Oryza sativa L.)

Abstract: Root uptake of atrazine (ATR) by rice seedlings (Oryza sativa L.) from nutrient solution was investigated with exposure periods of 48, 96, and 240 h. A similar ATR uptake was carried out with two co-existing organic compounds (o-chlorophenol (CP) and 2,4-dichlorophenol (DCP)) with 48 h exposure. In contact with the seedlings, the ATR level in nutrient solution decreased sharply during the early exposure and then reached relatively steady levels after 48 h. It was observed that the ATR levels within whole seedl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…The accumulation of azoxystrobin in wheat roots, stems, and leaves was linearly related to its concentration in the medium with R 2 values of 0.9682, 0.9193, and 0.9778, respectively. Similarly, Su et al found that rice showed linear uptake of atrazine at different concentrations …”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…The accumulation of azoxystrobin in wheat roots, stems, and leaves was linearly related to its concentration in the medium with R 2 values of 0.9682, 0.9193, and 0.9778, respectively. Similarly, Su et al found that rice showed linear uptake of atrazine at different concentrations …”
Section: Resultsmentioning
confidence: 89%
“…Similarly, Su et al found that rice showed linear uptake of atrazine at different concentrations. 35 The RCF was always much larger than the SCF and LCF (Figure 3B). No significant variations in the values of the RCF, SCF, and LCF were observed, although there were slight shifts in their values depending on the exposed level of azoxystrobin.…”
Section: ■ Results and Discussionmentioning
confidence: 91%